Cancer incidence and cancer control in Mongolia: Results from the National Cancer Registry 2008–12. Issue 2 (24th October 2016) - Chimed, Tuvshinjargal; Sandagdorj, Tuvshingerel; Znaor, Ariana; Laversanne, Mathieu; Tseveen, Badamsuren; Genden, Purevsuren; Bray, Freddie
Abstract : Mongolia has a high burden from noncommunicable diseases, with cancer now the second leading cause of mortality. Given the paucity of situation analyses from the country, this study reports cancer data based on new cases 2008–12 from the National Cancer Registry of Mongolia covering the entire population (2.87 million). New cancer cases of 21, 564 were diagnosed over the 5‐year period, with a slight predominance of cases (52%) in men. Liver cancer was the leading cancer site in both sexes (ASRs of 114.7 and 74.6 per 100, 000 males and females), and responsible for almost two‐fifths of all cancer diagnoses, followed by cancers of stomach, lung and oesophagus in men and cervix, stomach and oesophagus in women. The cumulative risk of incidence for all cancers (27.7% and 20.8% in men and women, respectively) positions Mongolia above China (20.2% and 13.3%), below the United States (34.1% and 28.5%) and similar to Russia (26.1% and 19.1%). These figures shed light on the considerable magnitude of cancer in the country and the large fraction of cancers that can be prevented by lifestyle modifications and vaccine implementation. An expansion of activities of the cancer registry and the continued development of research are necessary steps in support of national cancer control planning in Mongolia. Abstract : What's new? While cancer is the second‐leading cause of death in Mongolia, little is known about the country's national or regional cancer trends. Using data from the National Cancer Registry of Mongolia, the authors of this report describe region‐specific cancer incidence and patterns in cancer type for a 5‐year period (2008–12). Comparisons with selected countries further show that Mongolia's cumulative cancer risk exceeds that of China but is lower than cumulative risk in the United States. Underlying explanations from major risk factors, including chronic hepatitis infection, alcohol consumption, and air pollution, raise the prospect for cancer prevention through heightened public awareness.